Safety of long‐term intranasal budesonide delivered via the mucosal atomization device for chronic rhinosinusitis. Issue 5 (2nd February 2017) - Manji, Jamil; Singh, Gurkaran; Okpaleke, Christopher; Dadgostar, Anali; Al‐Asousi, Fahad; Amanian, Ameen; Macias‐Valle, Luis; Finkelstein, Andres; Tacey, Mark; Thamboo, Andrew; Javer, Amin
Abstract : Background: Although short‐term use (≤2 months) of atomized topical nasal steroids has been shown to be safe and effective, the long‐term safety has yet to be demonstrated. The aim of this study was to determine the impact of long‐term topical budesonide treatment via the mucosal atomization device (MAD) on the hypothalamic‐pituitary‐adrenal axis (HPAA) and intraocular pressure (IOP). Methods: A cross‐sectional study of patients with chronic rhinosinusitis (CRS), with or without nasal polyposis, managed with daily nasal budesonide via MAD was conducted at a tertiary rhinology center. Patients using systemic steroids within 3 months of assessment were excluded. HPAA impact was assessed using the cosyntropin stimulation test for adrenal function and a survey of relevant symptomatology. Patients also underwent tonometry to assess for elevated IOP potentially related to corticosteroid use. Results: A total of 100 CRS patients were recruited with a mean budesonide treatment duration of 23.5 months (range, 6–37 months). Stimulated cortisol response was diminished in 3 patients (3%). No patients with adrenal suppression had relevant symptomatology. IOP was elevated in 6 patients (6%). Conclusion: These findings suggest that there is a risk of adrenal suppression and raised IOP associated with the long‐term use of topical nasal budesonide via MAD. Otolaryngologists should consider periodic surveillance for these adverse events in this patient cohort.